A HETERONORMATIVIDADE EM QUESTÃO NO ESPAÇO ESCOLAR - Carlos Igor de Oliveira Jitusumori (2021)
ABSTRACT This is doctorate research which proposes problematize how LGBT students, from a state public school in Mato Grosso do Sul, in Campo Grande city, studying high school, act in front of the subjection devices who are submitted, by the cultural and social conditions, in their sexuality and genre. It aims to understand how the subjects involved (teenagers) deal with the prejudice and exercise self-practice that impact and make tense the speech that the school is heteronormative. For that, at the first moment, it was necessary to approach the reality to be investigated and the knowledge from several aspects from the school community and the subjects who are part of this study, in the sense of detecting different representations which are assigned to this student’s group. The theoretical ballast comes from Foucault postulates, sustained by an empirical and analytical base, that procedures to be adopted privilege ethnographic aspects, such as the school routine and education, designed by the social and cultural practices, throw the different selection mechanisms that subsidize records which indicate students’ meanings, perceptions, narratives that position them as LGBT and also the teachers who were analysed during this research. The posted problem that the school is exclusively heteronormative, in the institution different facets are shaken duo to the several dynamics, practices and speech that happen along the research. This work rattles the restricted and naturalized view of a school concept. Keywords: Heteronormativity; Teenagers; LGBT; Self- practice; School.